Comparative study of mathematics teachers’ challenges in implementing differentiated instruction and deep learning in the merdeka curriculum - Puput; Verminus; Nurul Azkiya; Ahmad Yani T; Nurfadilah Siregar (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Background: The Merdeka Curriculum emphasizes student-centered learning by encouraging mathematics teachers to implement differentiated instruction and deep learning. Although both approaches aim to enhance meaningful learning experiences, their differing characteristics pose varied challenges in classroom practice. Aims: This study aims to analyze and compare the challenges faced by mathematics teachers in implementing differentiated instruction and deep learning within the context of the Merdeka Curriculum. Methods: This study used a qualitative approach with an exploratory comparative design within a single school context. Participants included five (N=5) mathematics teachers selected via purposive sampling. Data were gathered through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The analysis focuses on uncovering analytical patterns of teacher experience rather than broad statistical generalizations. Result: The findings indicate that differentiated instruction presents challenges related to limited instructional time for preparing varied learning materials, insufficient supporting resources, and complex classroom management due to diverse student activities. Meanwhile, challenges in implementing deep learning include limited teacher competency and preparedness, inadequate facilities and learning resources, insufficient technological skills, and the complexity of lesson planning. The fundamental difference lies in the type of load: DI emphasizes efficiency in time and resource management, whereas DL requires technological readiness and a deeper level of understanding. Conclusion: This study concludes that teacher readiness is shaped by the tension between workload and pedagogical depth. Success requires structural shifts such as block scheduling and collaborative design hubs to allow teachers to transition from being classroom logisticians to architects of deep reasoning.